1997
DOI: 10.1007/s004420050128
|View full text |Cite
|
Sign up to set email alerts
|

Parental quality and egg size affect chick survival in a precocial bird, the lapwing Vanellus vanellus

Abstract: Effects of egg size and parental quality on lapwing Vanellus vanellus chick survival were studied in southwestern Sweden over 6 years. Chicks from large eggs were heavier at hatching and survived significantly better than those from small eggs. To control for the confounding effect of parental quality on egg size and chick survival, we performed a cross-fostering experiment during 2 years, exchanging clutches between nests with large and small eggs. In control clutches, chicks from large eggs survived better t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
102
0
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(113 citation statements)
references
References 34 publications
5
102
0
6
Order By: Relevance
“…Reid and Boersma (1990) found that higher-quality Magellanic Penguins (Spheniscus magellanicus) tended to have larger eggs that provided greater fitness because of increases in early chick survival. Blomqvist et al (1997) reported a similar result in the Northern Lapwing.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Reid and Boersma (1990) found that higher-quality Magellanic Penguins (Spheniscus magellanicus) tended to have larger eggs that provided greater fitness because of increases in early chick survival. Blomqvist et al (1997) reported a similar result in the Northern Lapwing.…”
Section: Discussionsupporting
confidence: 61%
“…This requires a female to give up a large proportion of her body mass in a relatively short period of time, which can cause an energetic strain (Monaghan and Nager 1997). However, it will likely improve her fitness, as it has been shown in many shorebird species that larger eggs produce larger chicks (Ricklefs 1984), and in the Charadriiformes larger chick size has been linked to improved chick survival (Parsons 1970, Blomqvist et al 1997, Dinsmore 2008.…”
Section: Inversión En El Tamaño Del Huevo En Un Ave Con Incubación Unmentioning
confidence: 99%
“…Peso do ovo (kg) 1,34±0,11 Peso vivo (kg) 0,79±0,16 Tarso-metatarso direito (cm) 7,03±0,86 Tarso-metatarso esquerdo (cm) 6,99±0,86 Cernelha (cm) 21,86±3,00 alimentares (BLOMQVIST et al, 1997;REED et al, 1999). Se tal estratégia é válida para avestruzes, ainda não existem evidências.…”
Section: Características Morfométricas Médiaunclassified
“…As dimensões do ovo (diâmetro maior e menor) são fortemente correlacionadas com o peso (BLOMQVIST et al, 1997), sendo este último recomendado como medida de tamanho do ovo para aves ratitas (Struthioniformes), por ser um método rápido e confiável (DI CAMPOS et al, 2005). A maior parte do peso do ovo, logo após a postura, deve-se à quantidade de albúmen e à proporção de água (FINKLER et al, 1998;DZIALOWSKI & SOTHERLAND, 2004).…”
Section: Introductionunclassified
See 1 more Smart Citation